Electromagnetic field excitation by an electron bunches in a partially filled cylindrical dielectric resonator - Galaydych, K.V.; Sotnikov, G.V.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2015)
A nonlinear self-consistent theory of wakefield excitation by an electron bunches in cylindrical resonator with longitudinally nonuniform filling by dielectric is constructed. A bunch-excited field are presented in the form of superposition solenoidal and potential fields. The formulated nonlinear theory allows carrying out numerical analysis of resonator excitation by electron bunches for the best interpretation of the results received in experiment. Построена нелинейная самосогласованная теория возбуждения кильватерного поля электронными сгустками в цилиндрическом резонаторе с продольно-неоднородным диэлектрическим заполнением. Возбуждаемое поле представлено в виде суперпозиции потенциального и соленоидального полей. Разработанная теория позволяет провести численный анализ возбуждения резонатора электронным сгустком для наилучшей интерпретации полученных экспериментальных результатов. Побудовано нелінійну самоузгоджену теорію збудження кільватерного поля електронними згустками в циліндричному резонаторі з поздовжньо-неоднорідним діелектричним заповненням. Поле, що збуджується, представлено у вигляді суперпозиції потенційного та соленоїдального полів. Розроблена теорія дозволяє провести числовий аналіз збудження резонатора електронним згустком для найліпшої інтерпретації отриманих експериментальних результатів.